2013
DOI: 10.1097/qad.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Preconception care for people living with HIV

Abstract: Globally, research has documented high fertility desires and intentions among HIV-positive women. Improving implementation of preconception care (PCC) for people living with HIV is critical, given estimates that the majority of HIV-positive women who want future biological children have not received reproductive counseling, largely due to a lack of provider-initiated conversations. This article offers initial recommendations and outlines key considerations for a research agenda to advance PCC implementation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…Thus, although all providers should be trained to counsel clients on basic safer conception principles (e.g. delay conception attempts until the infected partner is on ART), subsequent referral system to a designated, available provider who can offer in-depth advice may be acceptable to clients (66). Public health campaigns to improve awareness of safer conception strategies for the general population are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although all providers should be trained to counsel clients on basic safer conception principles (e.g. delay conception attempts until the infected partner is on ART), subsequent referral system to a designated, available provider who can offer in-depth advice may be acceptable to clients (66). Public health campaigns to improve awareness of safer conception strategies for the general population are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data published on physician attitudes regarding childbearing in HIV-infected women (Steiner, Dariotisa et al, 2013, Steiner, Finocchario-Kessler, & Dariotis, 2013; Yudin et al, 2012). Based on this study, we recommend that additional strategies are identified to enhance the dissemination and implementation of PCC protocols for HIV-infected women across the specialties of HIV medicine, OB/GYN, and primary care.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…PCC is also recommended when there is a change in a woman’s relationship status, or she is taking medications with potential reproductive toxicity or interaction with hormonal contraceptives (Panel on Treatment, 2014). Despite recommendations, protocols, and brochures to guide PCC in HIV care, counseling appears to be infrequently or cursorily addressed by health-care providers (Nattabi, Li, Thompson, Orach, & Earnest, 2009; Steiner, Dariotisa, Anderson, & Finocchario-Kessler, 2013). As few as 31% of HIV-infected women may receive a personalized discussion with their HIV provider regarding their own fertility desires and intentions, the majority of whom (64%) may have to initiate the conversation themselves (Finocchario-Kessler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which safer conception services are being offered in high-burden, resource-limited settings is unknown, and the outcomes of such services remain unreported [23]. Building an evidence base for safer conception strategies will be necessary before services can be rolled out across Sub-Saharan African (SSA) countries.…”
Section: Introductionmentioning
confidence: 99%